THU0519 Chronicity of Rheumatoid Arthritis Affects the Responsiveness of Physical Function, but not of Disease Activity Measures in Rheumatoid Arthritis Clinical Trials. (23rd January 2014) - Aletaha, D.; Alasti, F.; Smolen, J. S.
Abstract : Background: It has been shown that functional measures in rheumatiod arthritis (RA) are less responsive in patients with established or late disease as compared to early RA, because chronic irreversible functional damage is present. 1 They thus may not be useful as disease activity measures. Objectives: We aimed to investigate whether this finding is specific to functional measures, or if it similarly also relates to other RA disease activity measures. Methods: We performed a pooled analysis of patient level clinical trial data of patients with early, established, and late RA, including the TEMPO trial, the European leflunomide trials, the ATTRACT, and the DE019 trials. Using logistic regression analysis, we investigated the effects of duration of RA on the ability to achieve a 25% response at six months in the individual RA core set measures. Moreover, we performed a number of sensitivity analyses to support our findings. Results: The probability of response in functional scores decreased from >60% in early disease to <40% in established/late disease (p=0.0023; see Figure). No such association of responsiveness with chronicity of RA was seen in any of the other core set variables or composite indices (Figure). The effect of chronicity solely on functional responses was confirmed in all sensitivity analyses, including the use of structural chronicity (i.e. using radiographic damage) instead of temporal chronicity, the use of a 50% response level instead of 25%, as well as using the 3 month instead of the 6 month time point of response assessment. Image/graph: Conclusions: While physical function is among the most important outcomes of RA, its use as a substitute for disease activity is erratic depending on the chronicity of RA. Here it was shown for the first time that this phenomenon is specific to functional measures, but does not apply to any other core set measure of RA disease activity. References: Measuring function in rheumatoid arthritis: Identifying reversible and irreversible components. Arthritis Rheum 2006; 54(9):2784-2792. Acknowledgements: We thank Abbott, Centocor (Janssen), Sanofi-Aventis, and Wyeth (Pfizer), for providing the random sample of the original data from their trials. Disclosure of Interest: None Declared